PERANCANGAN SISTEM INFORMASI PENGADUAN SAMPAH BERBASIS WEB DI DINAS KANTOR LINGKUNGAN HIDUP ENDE - More, Yohanes Rede (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
The ineffectiveness and slow process of complaining about garbage at the Environmental Service led me to take the initiative to create a website-based waste complaint system so that it would make it easier for the relevant departments to serve public complaints about waste in the city of Ende and also so that people can make complaints about garbage more quickly through the created website. By directly observing the waste complaint process at the Environmental Service, conducting interviews with the Head of the Environmental Service's Garbage Division about the waste complaints used, Requesting the flow of the garbage complaint system that runs in the office. Based on this problem, the authors offer a solution to solve this problem by creating a web-based waste complaint system so that it can facilitate the relevant agencies in serving public complaints regarding waste in the city of Ende. Then test the system created using the Blackbox Testing method. From the results of making a garbage complaint information system, it can be concluded that the complaint system using the web can run well and is computerized. Keywords: Environmental Service, Garbage Complaints, Website-based.